2016
DOI: 10.1007/s10964-016-0608-x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Perceived Stress and Self-Efficacy in Young People’s Life Satisfaction: A Longitudinal Study

Abstract: Life satisfaction is an important indicator of successful development. However, adolescents' life satisfaction tends to be relatively unsteady, and environmental influences play a critical role in shaping life satisfaction among adolescents in the transition to young adulthood. Given the paramount importance that education plays in adolescents' lives, adolescents' life satisfaction may vary as a function of school-related stress experience. At the same time, coping resources may help reduce adverse effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
104
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 84 publications
(80 reference statements)
12
104
0
8
Order By: Relevance
“…Self‐efficacy is also a key factor in attaining behavioural goals (Nc et al, ). With higher self‐efficacy, adolescents with T1D may be more confident about self‐management, their ability to successfully commit to plan and meet targeted goals (Burger & Samuel, ; Francis, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐efficacy is also a key factor in attaining behavioural goals (Nc et al, ). With higher self‐efficacy, adolescents with T1D may be more confident about self‐management, their ability to successfully commit to plan and meet targeted goals (Burger & Samuel, ; Francis, ).…”
Section: Discussionmentioning
confidence: 99%
“…With higher self-efficacy, adolescents with T1D may be more confident about self-management, their ability to successfully commit to plan and meet targeted goals (Burger & Samuel, 2016;Francis, 2015).…”
Section: Ta B L E 2 Estimated Regression Coefficients For Equation (3mentioning
confidence: 99%
“…Although research on the role of LS in relation to adolescent stress experience remains limited, along with major life events (2), minor chronic everyday stressors correlate negatively with LS (8,10,(12)(13)(14). In the school context, experience of high academic stress and negative interactions with teachers correlate with lower LS (9,12,13,15). Life satisfaction also correlates with several interpersonal factors in adolescents' lives, including the quality of parent and peer relationships (2,7,16).…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy can thus be regarded as an important coping resource in the face of different stressors, that affects emotional and cognitive processes as well as choice of coping strategies (14,20,21,24); potentially this may reduce the negative impact of stress on health and wellbeing (23,25). In studies with adults and adolescents, self-efficacy has been shown to relate negatively with mental health problems such as depression, anxiety and perceived helplessness (25,26) and positively with quality of life (27,28) and LS (2,9,(29)(30)(31)(32). Moreover, when gender differences are found, males score higher than females do on self-efficacy (21,25,32).…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that not only an effective achievement, but even a subjective perception of progress and a sense of movement in the right direction towards the goal, leads to increasing subjective well-being (Wiese, 2007). LS is also associated with such personal characteristics which characterize first of all the person's activity in achieving goals and overcoming difficulties: motivation for achievement, self-efficacy, stress resistance, self-control (Bandura, 1993;Burger, & Samuel, 2017;Hofmann et al 2014). With regard to learning activities, self-regulation is an important predictor of the education success (Zimmerman, 1990), which in turn allows to say that development of students' self-regulation can be a necessary condition for the children psychological well-being in school.…”
Section: Introductionmentioning
confidence: 99%